Four new species of Cystolepiota (Agaricaceae, Agaricales) from northeastern China - Zhou, Xian-Yan; Bau, Tolgor (Frontiers in Microbiology, 2024)
Cystolepiota is a tiny lepiotaceous fungi. During our 3 years fieldwork, we found four new species of Cystolepiota from northeastern China. A phylogenetic study of a combined dataset of ITS+nrLSU+rpb2+tef1-α revealed that Cystolepiota changbaishanensis and Cystolepiota hetieri are sister clades; Cystolepiota hongshiensis belongs to Cystolepiota seminuda complex; Cystolepiota luteosquamulosa formed a clade not closely related with any other; Cystolepiota nivalis and Cystolepiota sp. (HMJAU68235) formed a sister clade. All new species are provided with descriptions, photos of the basidiomata, and colored illustrations of the microstructures. A key for the identification of Cystolepiota species from China is also presented.